Sorption Promoters: A Novel Enhancer Approach for Topical Drug Delivery System - Singh, R. P.; Parpani, S.; Narke, R.; Chavan, R. (Asian Journal of Pharmaceutical Research and Development, 2014)
Topical drug delivery system can be defined as direct effects of formulation or drug containing medication to the skin to get localizing effect of drug or directly cure cutaneous disorders. The skin has evolved to prevent excessive water loss from the internal organs and to limit the ability of xenobiotics and hazardous substances to enter the body. Notwithstanding this barrier function, a number of strategies have been developed by scientists to deliver drugs to and through the skin. Skin as an important site for topical effects so there is considerable interest in the skin for local and systemic effect of drug application. However, in the skin, the stratum corneum is the main barrier for drug penetration there by limiting topical and transdermal bioavailability. Skin penetration enhancement techniques have been developed to improve bioavailability and increase the range and number of drugs available for both topical and transdermal delivery. In this review, we have discussed about the various penetration enhancers, their mechanism of action and their potential for clinical application.